2004
DOI: 10.1097/00007691-200406000-00019
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Approximation for Busulfan Dose Adjustment in Adult Patients Undergoing Bone Marrow Transplantation

Abstract: Busulfan is an alkylating agent used in preparative regimens before bone marrow transplantation (BMT). Busulfan concentrations in plasma, expressed as the area under the concentration-time curve (AUC), were reported to correlate with treatment outcome. Because busulfan is administered in 16 doses of 1 mg/kg every 6 hours for 4 days, the opportunities to "correct" the dose as a consequence of the measured AUC are limited to the 16-dosage protocol. In the present research busulfan pharmacokinetics were prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Open and closed circles represent the value in adults and children, respectively. 20,23,26 To compare our data with the oral busulfan studies in adult patients, we used previously published data. 23 The selected study has similar sampling points to our study and individual AUC were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open and closed circles represent the value in adults and children, respectively. 20,23,26 To compare our data with the oral busulfan studies in adult patients, we used previously published data. 23 The selected study has similar sampling points to our study and individual AUC were reported.…”
Section: Discussionmentioning
confidence: 99%
“…20,23,26 To compare our data with the oral busulfan studies in adult patients, we used previously published data. 23 The selected study has similar sampling points to our study and individual AUC were reported. Several reports indicate that an AUC of 900-1500 mmol min/l 4,6,24,25 in patients receiving a conventional busulfan regimen prevents treatment failure and the risk of fatal toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Busulfan, in combination with cyclophosphamide or fludarabine, is commonly used in preparatory regimens before allogenic or autologous hematopoietic stem cell transplantation (HSCT) [3][4][5][6][7]. The primary molecular reaction for biologic activity is the alkylation of intra-cellular nucleophiles.…”
Section: Drug Properties and Mechanism Of Actionmentioning
confidence: 99%
“…The usual oral dose was established to be 1 mg/kg and 1.2 mg/kg for a total of 16 doses in adult and pediatric patients, respectively [5,7,9,28,50]. Several authors have demonstrated that oral [5,6] and intravenous [32] busulfan has relatively linear pharmacokinetics allowing dose adjustment and conditioning treatment optimization using a simple pocket calculator [7,32]. According to basic principles linear pharmacokinetics implies that drug concentration increases in direct relation with the given dose.…”
Section: Area Under the Concentration-time Curve (Auc) For Hematopoiementioning
confidence: 99%
“…1 Também, devido as suas propriedades mielossupressivas, é um dos medicamentos mais frequentemente utilizados em regime de altas doses em combinação com outros agentes, como a ciclofosfamida, no tratamento mieloablativo do pré-transplante de medula óssea. [1][2][3][4] Como a maioria dos agentes alquilantes, o BU apresenta uma janela terapêutica estreita e pode ter sua biodisponibilidade influenciada por fatores como idade, obesidade, ritmo circadiano e variabilidade farmacocinética intraindividual. 5 Concentrações abaixo da faixa terapêutica recomendada (concentrações em estado estacionário entre 800 a 900 ng mL -1 ) estão associadas à recorrência da doença ou à rejeição do transplante, indicando ablação incompleta da medula.…”
Section: Introductionunclassified